Propolis and Its Combination with Boric Acid Protect Against Ischemia/Reperfusion-Induced Acute Kidney Injury by Inhibiting Oxidative Stress, Inflammation, DNA Damage, and Apoptosis in Rats - Geyikoglu, Fatime; Koc, Kubra; Colak, Suat; Erol, Huseyin Serkan; Cerig, Salim; Yardimci, Berna Kavakcioglu; Cakmak, Ozge (Humana Press Inc, 2019)
Ischemia reperfusion (I/R) injury which causes kidney dysfunction is one of the most studied diseases directly linked to oxidative stress. In this regard, it is important to protect cells against damage by inducing antioxidant response. Herein, we aimed to evaluate the therapeutic roles and possible mechanisms of propolis and boric acid in kidney I/R injury based on relevant basic research and clinical studies. Sprague-Dawley rats were subjected to 50 min of ischemia followed by 3 h of reperfusion. Animals were randomly divided into a control group (the abdominal wall was just opened and closed), an I/R injury group, the propolis intervention group (200 mg/kg, intragastric administration, 1 h before ischemia), boric acid intervention group (14 mg/kg, intragastric administration 1 h before ischemia), and the propolis + boric acid intervention group (intragastric administration 1 h before ischemia). Kidney function, the antioxidant defensive system, and renal damage were assessed. In addition, the oxidative stress and inflammatory status were estimated in renal tissue. Furthermore, DNA damageand apoptosis were detected by immunohistochemistry. When compared with I/R group, propolis alone and especially propolis + boric acid groups significantly improved functional parameters. While the antioxidant response was increased, renal injury size and apoptosis were significantly decreased in both groups. Also, the MDA and TNF-alpha levels besides the 8-OHdG formation were downregulated. According to these outcomes, it can be said that especially propolis together with boric acid ameliorates kidney injury caused by I/R through acting as an antioxidant, anti-inflammatory, and antiapoptotic agent. In conclusion, propolis alone and its combination with boric acid could be developed as therapeutic agents against serious renal I/R injuries.
Keywords: Ischemia/Reperfusion; Propolis; Boric Acid; Kidney; Oxidative Stress; Inflammation